Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1001/archpedi.156.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rapid Diagnosis of Influenza Virus Type A on the Emergency Department Management of Febrile Infants and Toddlers

Abstract: Rapid confirmation of influenza virus type A infection seems to decrease ancillary tests and antibiotic use in febrile infants and toddlers in the ED. A prospective study with a larger group is needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
62
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 15 publications
5
62
1
3
Order By: Relevance
“…Fever, cough and acute onset were found to be most useful predictors of influenza infection in adults [17,20,21]. In the present study, univariate analysis showed that adult patients with fever ≥38°C, cough and abnormal breathing sounds were 2.6, 3.09, and 1.7 times more likely to have influenza.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…Fever, cough and acute onset were found to be most useful predictors of influenza infection in adults [17,20,21]. In the present study, univariate analysis showed that adult patients with fever ≥38°C, cough and abnormal breathing sounds were 2.6, 3.09, and 1.7 times more likely to have influenza.…”
supporting
confidence: 49%
“…Yet, influenza infection is a considerable cause of morbidity and health care utilisation in paediatric population. Attack rates in healthy children are estimated to be between 10% and 40% [21]. There is a wide range of clinical symptoms associated with influenza in infants and toddlers, making the clinical management difficult.…”
mentioning
confidence: 99%
“…Moreover, rapid identification of influenza cases may contribute to the limitation of unnecessary antibiotic use and prevention of nosocomial transmission of the virus to high risk hospitalized population groups [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…(10) Some small studies have shown that a positive RAT spurs changes in clinical practice. (11)(12)(13) In this study, we investigated the effect of RAT for influenza on the proportion of antibiotic administration, additional diagnostic tests, and the length of stay (LOS) in the ED. The symptoms investigated included shivering, rhinorrhea, headache, sore throat, malaise, cough, sputum, myalgia, and gastrointestinal symptoms.…”
Section: Introductionmentioning
confidence: 99%